2020
DOI: 10.15407/cryo30.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Antarctica: from the Sleep Disturbances Towards All the Challenges

Abstract: Sleep in Antarctica: from the Sleep Disturbances Towards All the Challenges Реферат: С первых экспедиций адаптация их участников к суровым условиям Антарктиды сопровождалась жалобами на нарушения сна. В ходе длительного пребывания на континенте полярники подвергаются воздействию большого количества экстремальных факторов окружающей среды как на станции, так и вне ее пределов, но основными физическими причинами, вызывающими нарушения сна, принято считать особенности освещенности и фотопериода. В последнее время… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…Antarctica is a unique place to study health conditions under the influence of environmental factors on the organism in pure form [ 10 , 11 , 12 , 13 , 14 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Antarctica is a unique place to study health conditions under the influence of environmental factors on the organism in pure form [ 10 , 11 , 12 , 13 , 14 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medical research in Antarctica opens up new horizons of understanding across a spectrum of individual health conditions under stress and unusual environmental conditions [ 24 ]. The series of the retrospective and prospective studies demonstrated the strong influence of extreme environmental factors and stress in the absence of man-made factors on health parameters, with clearly defined individually patterned reactions [ 10 , 11 , 12 , 13 , 14 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Отже, визначені особливості субклітинних та молекулярних перебудов у антарктичних зимівників дають змогу поглиб лено оцінювати стан адаптаційних проце сів і можуть бути додатковим критерієм при медичному відборі кандидатів до антарктичної експедиції, прогнозування негативних наслідків тривалого впливу екстремальних факторів та діагностики прихованих порушень [12].…”
Section: результати та їх обговоренняunclassified